Host–Guest‐Induced Environment Tuning of 3d Ions in a Polyoxopalladate Matrix - Stuckart, Maria; Izarova, Natalya V.; van Leusen, Jan; Smekhova, Alevtina; Schmitz‐Antoniak, Carolin; Bamberger, Heiko; van Slageren, Joris; Santiago‐Schübel, Beatrix; Kögerler, Paul (Chemistry : a European journal, 2018)
A series of unprecedented supramolecular associates of phenylarsonate‐capped MIIPdII12O8‐type (M=Co, Ni and Zn) polyoxopalladates with α‐cyclodextrins (α‐CD) was obtained and characterized in the solid state (single‐crystal X‐ray diffraction (XRD), FT‐IR spectroscopy, elemental and thermogravimetric (TGA) analyses), in aqueous solution (1H and 13C NMR) and in the gas phase (ESI‐MS). The non‐covalent host–guest interactions between the organopolyoxoanions and α‐CD rings alter the O8 coordination environment of a 3d transition metal ion (MII) situated at the center of a cuboid polyoxododecapalladate shell. This synthetically controlled “chemical pressure” effectively induces axial distortion of the otherwise cubic polyoxopalladate environment between two trans‐positioned α‐CD moieties. Its effect on the magnetic properties and the electronic structure of the CoII derivative was assessed in a combined SQUID magnetometry, EPR, X‐ray magnetic circular/linear dichroism (XMCD/XMLD), and X‐ray absorption near‐edge structure (XANES) spectroscopy study. The sweet pressure is on (the noble cube): Modification of the coordination environment of the transition metal ion incorporated in the center of a polyoxometalate cage can be achieved via non‐covalent interactions, as demonstrated by a novel family of supramolecular {MPd12(AsPh)8}⊂2(α‐CD) host–guest associates of transition‐metal‐centered, phenylarsonate‐capped polyoxopalladates with α‐cyclodextrins.